Rancang Bangun Aplikasi Sistem Pakar Untuk Diagnosis Penyakit Asma Dan Gangguan Pernafasan - Tohir, Andi Rahmatulloh; Sukmaaji, Anjik; Lemantara, Julianto (Jurnal JSIKA, 2012)
Asthma and respiratory disorders one type of disease affecting humans. Based on interviews with the doctors at the lungs poly Dr. Soetomo public hospital, a variety of asthma and respiratory disorders have many symptoms that are similar and some have only differentiated by only one symptom. Required accuracy and sharp analysis for a doctor to reveal a type of asthma in order to give appropriate treatment to the patient. One way to overcome the problems above is by designing a rule-based system for the problems of asthma and respiratory disorders. By using the facts provided by the user the system can produce a conclusion which is representation of forward chaining method to begin tracking the data or facts that exist towards a conclusion. Based on the findings of the obtained results, the expert system for diagnosis of asthma and respiratory disorders may help doctors in lungs poly Dr. Soetomo public hospital. This system can provide assistance in the form of conclusion types of asthma and respiratory problems as well as the implementation of treatments and therapies for patients with asthma and respiratory disorders